Filozofická reflexe omezené racionality (Philosophical Reflection of Bounded Rationality ) - Michal Müller; Ondrej Močkor (Ostium, 2017)
Research of rationality represents area of interaction between philosophy and economics. Development of neuroscience and advances in scientific research lead to another common characteristic – gradual loss of competence to comment on results of scientific research. This article describes development of the concept of economic rationality and makes an effort to deal with the following question: Can philosophy play useful role in contemporary discussions about the nature of decision-making and rationality? The authors conclude that philosophy itself does not have any extraordinary method which is able to ensure an exclusive position within the contemporary research. The role of philosophy consists in analyzing arguments, explanations of terms, in the search for ethical consequences, or in the preparation of social sciences to naturalization through critical evaluation of obsolete approaches that are inconsistent with the findings of natural science.